Amyand's Hernia in a 6-Week-Old Infant: A Delayed Diagnosis - Cláudia Piedade; Júlio Reis Alves (Hindawi Limited, 2013)
In Amyand's hernia, the hernia sac contains the appendix. This can be normal and accidentally found during herniotomy or inflamed and present as acute scrotum, although the latter is less frequent. We present a case of a male infant with scrotal abscess resulting from Amyand's hernia, with appendicitis and periappendicular abscess.